Changing pattern in incidence and management of paediatric inflammatory bowel disease in southwest of England from 1997 to 2007. (29th September 2015) - Hosdurga, S; Basude, D; Spray, C; Gardner, C; Sandhu, B
Abstract : Introduction: In 1997, a national prospective survey (British Paediatric Surveillance Unit (BPSU)) of childhood (<16 years) inflammatory bowel disease (IBD) in the UK provided the best international prospective incidence data of a large IBD cohort; it documented a national incidence of 5.2 /100 000. 33 children were from the South West (SW) region. It is not possible to repeat the national study because the numbers are large. Hence a regional audit was designed. Aims: (1) To document the current incidence of IBD and analyse the changes compared to the BPSU survey; (2) whether children are being diagnosed in concordance with ESPGHAN's Porto criterion and receiving appropriate treatment in line with best practice (BSPGHAN Guidelines on management of IBD, 2008). Methodology: Data were collected from 13 paediatric centres in the South West using international diagnosis codes (ICD10) identifying newly diagnosed cases of IBD including Crohn's disease (CD), ulcerative colitis (UC) and indeterminate colitis (IC). Patient details were correlated with departmental database. The population data were obtained from the office of National Statistics. This project is approved by the local audit committee. Results: All 13 centres responded. There were 51 newly diagnosed children with IBD during 2007 compared with 33 in 1997. 45 cases were diagnosed at the regional centre and were on the database; 6/51 from two centres were not. The details of the incidence figures are given in the following table 1 . 43 cases were analysed in detail. 17.6% of cases had an input by an adult surgeon. Time interval from symptoms to referral to a paediatric gastroenterologist is a mean of 9.9 months (1–58 months) and time interval from symptoms to treatment is 13.8 months. 97% of CD and IC cases had barium meal studies. 39/43 (90.6%) had full colonoscopy. Upper GI involvement was seen in 35% and pancolitis in 27%. 70% of CD cases were treated with diet. Conclusion: There is a definite increase in the incidence of paediatric IBD in the SW England. The increase is not only in the number of CD but more significantly in UC. The IC incidence remains stable. There is a significant delay in time period from onset of symptoms to referral to a paediatric gastroenterologist.